MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI MENGENAL MACAM-MACAM SUDUT MENGGUNAKAN MEDIA PEMBELAJARAN PERMAINAN ULAR TANGGA - Dea Fariska Ardiana Samsudin; Octarina Hidayatus Sholikhah; Upik Wahyuni Nawang Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to improve students' mathematics learning outcomes using snakes and ladders learning media on the material of recognizing various angles in class III in elementary schools. The methods used in this research are qualitative and quantitative. The data collection technique used was observation, testing and documentation techniques. Data were analyzed by data reduction, data presentation, and drawing conclusions. The learning media for the snakes and ladders game is a game that can be played by all children without using an internet network. In the snakes and ladders game there are two cards containing question cards and material cards. Both cards can be taken by students alternately. The game is played in groups of 4-5 students. The snakes and ladders game is played using pawns and moves using dice as a reference for the number that students must pass. This media is provided to increase students' interest in the material about various angles. This snakes and ladders game is a learning medium that can be made easily and fun for students in elementary schools. The mathematics learning outcomes of students using the snake and ladder game learning media show increased learning outcomes. It can be seen in the results of students' learning completeness of 9.09%. In the implementation of Action Cycle 1, students' learning completeness increased to 31.82%. In the implementation of cycle 2 actions, learning outcomes increased by 68.18%. The results of observations during class actions showed that students looked very enthusiastic in participating in learning using the learning media of the snakes and ladders game which has been proven to improve student learning outcomes.